Persuasive Acts in the AsianGuyStream’s YouTube Contents - Gabriella Novainty Soedjarwo; Gabriella Inggita Saskara (UIN Salatiga, 2024)
Skill and strategy are essential in persuasion. By implementing appropriate strategy and having a good speaking skill can make someone be a good persuader. Successful persuasion can even move other people to do almost anything. Studying persuasion is under the notion of pragmatics since pragmatics studies the use of language in certain context, in this case the context is persuasive attempt. Atsu, the famous Genshin Impact content creator, implement the hope theory in persuade his viewers to keep wishing. This theory is an appropriate strategy since in Genshin Impact, players need to spend game resource even money if they want to maximize the character and weapon’s potential through wishing. This system is so-called gacha; in gacha games, the players do not know exactly what they get. thus Atsu kept giving hope to the viewers that they will get the rewards after spending much resources or money. This strategy is shown to be successful since Atsu, most of the time, was successfully delivered his persuasive attempt. The data was taken from the videos uploaded in his YouTube account under the name of AsianGuyStream. The data was stored by screenshotting the persuasive expression and analyse them using hope theory and visual aids.